The Effect of Antigibberellin Cultar , Ethaphon and Gbberellin on Surface Growth of Rhizoctonia so/ani and Fusarium oxysporum - AI-Qaisi, W.A; Janabi, S.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was conducted to study the effect of antigibberellin Cultar , Ethephon and GA3 at concentration of (5,15,25 ppm) on surface growth of Rhizoctiona solani and Fusraium oxysporum . The results indicated that Cultar (15 , 25 ppm) decreased the surface growth of both fungi . Ethephon of the same concentration significantly reduced the growth of Fusarium oxysporum . The number of sclerotia of Rhizoctiona solani was reduced by Cultar and GA3 at (15 ,25 ppm).